Multiple endocrine neoplasia type 2: A review. (February 2022) - Mathiesen, Jes Sloth; Effraimidis, Grigoris; Rossing, Maria; Rasmussen, Åse Krogh; Hoejberg, Lise; Bastholt, Lars; Godballe, Christian; Oturai, Peter; Feldt-Rasmussen, Ulla
Abstract: Multiple endocrine neoplasias are rare hereditary syndromes some of them with malignant potential. Multiple endocrine neoplasia type 2 (MEN 2) is an autosomal dominant hereditary cancer syndrome due to germline variants in the RE arranged during T ransfection ( RET ) proto-oncogene. There are two distinct clinical entities: MEN 2A and MEN 2B. MEN 2A is associated with medullary thyroid carcinoma (MTC), phaeochromocytoma, primary hyperparathyroidism, cutaneous lichen amyloidosis and Hirschprung's disease and MEN 2B with MTC, phaeochromocytoma, ganglioneuromatosis of the aerodigestive tract, musculoskeletal and ophthalmologic abnormalities. Germline RET variants causing MEN 2 result in gain-of-function; since the discovery of the genetic variants a thorough search for genotype-phenotype associations began in order to understand the high variability both between families and within family members. These studies have successfully led to improved risk classification of prognosis in relation to the genotype, thus improving the management of the patients by thorough genetic counseling. The present review summarizes the recent developments in the knowledge of these hereditary syndromes as well as the impact on clinical management, including genetic counseling, of both individual patients and families. It furthermore points to future directions of research for better clarification of timing of treatments of the various manifestations of the syndromes in order to improve survival and morbidity in these patients.